Registered Nurse Prescribing in Ontario: Learners’ Perspective - Morrell, Sherry; Pittman, Gina; Ziegler, Erin; Simanovski, Jane; Horton, Amy; Sheppard-LeMoine, Debbie; Abu Rashid, Hala; Mammarella, Ava; Abdulmoula, Ibrahim; Al-Hamdani, Mustafa (Quality Advancement in Nursing Education / Avancées en formation infirmière, 2025)
Background: In response to evolving health care demands and the increasing need for accessible patient care, eight Canadian provinces have expanded the scope of practice for registered nurses (RNs) to prescribe medications. Ontario is the latest province to approve RN prescribing. RNs with prescribing authority in Ontario can prescribe specific medications approved by the Ministry of Health and Long-Term Care and authorized by the College of Nurses of Ontario (CNO). RNs must complete one of the four available CNO Council–approved RN prescribing education programs to become an authorized prescriber in Ontario. As RN prescribing is new to Ontario, it is essential to assess the effectiveness of the educational programs preparing nurses for this new role.Purpose: A quality improvement project (QIP) was conducted to gain learners’ perspectives on one of Ontario’s CNO-approved RN Prescribing programs.Methods: This QIP focused on learners enrolled through the University Consortium RN Prescribing Program. Pre- and post-course surveys were administered via Qualtrics XM. Data collected included demographic information, motivation for enrolling in the program, employment plans related to the expanded scope of practice, familiarity with the new CNO Practice Standards, and confidence in prescribing safely. Pre- and post-course survey composite scores were computed to reflect participants’ overall familiarity with the RN prescribers’ scope of practice and their confidence in their ability to prescribe safely within the scope of practice. We conducted Mann-Whitney U non-parametric tests were conducted to determine any statistical difference between the median of the pre- and post-course composite scores (familiarity scores and confidence level).Results: A total of 194 pre-course and 136 post-course anonymous survey questionnaires were completed through Qualtrics XM. The baseline demographic characteristics were similar in pre- and post-course groups. Top motivators for taking the course were career advancement and personal goals. The median familiarity score for pre-course (2.50) and post-course (3.0) surveys was statistically significant (U = 4141.5, z = –10.93, p < 0.001). The median confidence score for pre-course (80.5) and post-course (85.0) surveys was not statistically significant (U = 11629, z = –1.843, p = –0.065).Conclusion: Upon completion of the course, learners in the University Consortium’s inaugural RN prescribing program reported increased familiarity with the scope of practice and confidence in their ability to prescribe safely. Introducing safe registered RN prescribing in Ontario can significantly advance health care by optimizing resource use, improving access to care, and enhancing patient-centred care.